HARDY'S INEQUALITIES IN FINITE DIMENSIONAL HILBERT SPACES - Dimitrov, Dimitar K. [UNESP]; Gadjev, Ivan; Nikolov, Geno; Uluchev, Rumen (Amer Mathematical Soc, 2021)
We study the behaviour of the smallest possible constants d(n), and c(n), in Hardy's inequalities Sigma(n)(k=1) (1/k Sigma(k)(j=1) a(j))(2) <= d(n) Sigma(n)(k=1) a(k)(2), (a(1), ..., a(n)) is an element of R-n and integral(infinity)(0) (1/x integral(x)(0) f(t) dt)(2) dx <= c(n) integral(infinity)(0) f(2)(x) dx, f is an element of H-n, for the finite dimensional spaces R-n and H-n := { f : f(o)(x) f(t)dt = e(-x/2) p(x) : p is an element of P-n,p(0) = 0}, where P-n is the set of real-valued algebraic polynomials of degree not exceeding n. The constants d(n) and c(n) are identified to be expressed in terms of the smallest zeros of the so-called continuous dual Hahn polynomials and the two-sided estimates for d(n) and c(n) of the form 4 - c/In n < d(n), c(n) < 4 - c/In-2 n, c > 0 are established.